Synchrotron scanning reveals amphibious ecomorphology in a new clade of bird-like dinosaurs - Cau, Andrea; Beyrand, Vincent; Voeten, Dennis F A E; Fernandez, Vincent; Tafforeau, Paul; Stein, Koen; Barsbold, Rinchen; Tsogtbaatar, Khishigjav; Currie, Philip J; Godefroit, Pascal (Nature, 2017)
Maniraptora includes birds and their closest relatives among theropod dinosaurs. During the Cretaceous period, several maniraptoran lineages diverged from the ancestral coelurosaurian bauplan and evolved novel ecomorphologies, including active flight, gigantism, cursoriality and herbivory. Propagation X-ray phase-contrast synchrotron microtomography of a well-preserved maniraptoran from Mongolia, still partially embedded in the rock matrix, revealed a mosaic of features, most of them absent among non-avian maniraptorans but shared by reptilian and avian groups with aquatic or semiaquatic ecologies. This new theropod, Halszkaraptor escuilliei gen. et sp. nov., is related to other enigmatic Late Cretaceous maniraptorans from Mongolia in a novel clade at the root of Dromaeosauridae. This lineage adds an amphibious ecomorphology to those evolved by maniraptorans: it acquired a predatory mode that relied mainly on neck hyperelongation for food procurement, it coupled the obligatory bipedalism of theropods with forelimb proportions that may support a swimming function, and it developed postural adaptations convergent with short-tailed birds.
Keywords: přední končetina; ptáci; Birds; Phylogeny; Swimming; Mongolia; Adaptation, Physiological; krk; Skull; Tail; Synchrotrons; zvířata; Mongolsko; Aquatic Organisms; fylogeneze; fyziologická adaptace; Neck; Animals; lebka; synchrotrony; vodní organismy; dinosauři; plavání; Dinosaurs; Forelimb; ocas